The Frequency of Postoperative Pain Among Patients Following Day-Case Surgery at a Hafr ElbatnHospital: A Cross-Sectional Study - Mashref Ytaim R Aldhafeeri, Omar Abdullah W Aloslib, Khalid Fazaa M Aldhafeeri, Mohammed Qasem Mohammed Alhazimi, Seadoun Raheel N Aldhafeeri, Fahad Eissa M Alanazi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This study aims to investigate the prevalence and progression of postoperative pain among patients undergoing day-case surgery at a Hafr Elbatnhospital, focusing on the early postoperative period at home.Methods: A total of 648 patients who underwent day-case surgery were included in the study over a 4-month period. Data were collected through interviews and questionnaires, with pain intensity measured using a visual analog scale (VAS) for 4 days post-surgery. Side effects of anesthesia and analgesia techniques were also documented.Results: On the day of surgery, 26% of patients reported moderate to severe pain (defined as mean VAS >40 mm). Mean VAS scores above 40 mm were observed in 21% of patients on postoperative day (POD) 1, 13% on POD 2, 10% on POD 3, and 9% on POD 4. Procedures involving the nose and pharynx, abdominal surgeries, breast plastic surgery, and orthopedic surgeries were identified as the most painful during the initial 48 hours post-surgery.Discussion: The study highlights that a significant proportion of patients experience moderate to severe postoperative pain even up to 4 days after day-case surgery. Additionally, the type of surgical procedure plays a crucial role in planning postoperative analgesia for ambulatory surgeries